Fire safety of wood-steel connections - Fonseca, Elza M M (2019)
The main objective of this work is to present different analytical and computational methods which permit the safe design calculation of the wood-steel connections, under fire conditions. Wood is an anisotropic, heterogeneous and porous material and its behaviour varies with temperature. The increase of temperature influences the progressive degradation of wood properties. During fire exposure, it is need to determine if the charred wood connections are safe in use. Design methods require the use of analytical methodologies and computational modelling to predict the fire exposure and the components capacity to resist to this action. In this work, the authors present studied cases, that will help professionals to analyse wood-steel connections and focus the type of information needed to decide whether the charred elements are adequate or not to use. For the same wood-steel connections, different insulation materials will be analysed to compare their behaviour and determine the fire resistance in time domain.